Brachistosternus ninapo a new species (Scorpiones: Bothriuridae) from western Andes in southern Peru - Ochoa, José Antonio (2004)
Brachistosternus ninapo, a new bothiurid species from western Andes of southern Peru (2900- 4050 m) is described. This species belongs to the subgenus Brachistosternus (Leptosternus) Maury. It is related to bolivian species Brachistosternus galianoae Ojanguren Affilastro, and differs from this, by the morphology of the hemispermatophore (shape of the lamina and some details in the lobe region), the number of dorsolateral setae on caudal segment V, the length/width ratio of the male chela and the pigmentation pattern of the tergites.